Adapting Server Systems for New Memory Technologies. - Hunter, Hillery; Lastras-Montano, Luis A.; Bhattacharjee, Bishwaranjan (Computer (00189162), 2014)
After decades of a cache, DRAM, and disk data storage hierarchy, new memory technologies are promising nonvolatility, high endurance, and fine-grained data access--all of which could, with some preparation, enable a new storage paradigm in server systems.